Genome annotation of Caenorhabditis briggsae by TEC-RED identifies new exons, paralogs, and conserved and novel operons - Nikita Jhaveri; Wouter van den Berg; Byung Joon Hwang; Hans-Michael Muller; Paul W Sternberg; Bhagwati P Gupta (G3: Genes, Genomes, Genetics, 2022)
AbstractThe nematode Caenorhabditis briggsaeCaenorhabditis elegansC. briggsaeC. briggsaetransC. briggsaeC. briggsaeC. elegansC. elegansC. elegansCaenorhabditis nigoni.C. briggsae